Implementing Pekanbaru Regulation No. 10/2021; Narcotics Prevention Case Study - Nia Kurnia Nesta; Febri Yuliani Yuliani (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2024)
The residents of Pekanbaru City are This study examines the implementation of drug prevention programs in Pekanbaru City, which are guided by Regional Regulation Number 10 of 2021, focusing on prevention efforts. Using George Edward III's implementation theory, the research identifies key barriers to successful program execution, such as limited budget, inadequate socialization, and insufficient human resources. These factors hinder effective communication and program activities. The study concludes that improvements in resource allocation, communication, and structural support are needed for more effective and comprehensive drug prevention efforts in the city.